126 Growing up, gaining independence: transition improvement. (December 2018) - Mills, N
Abstract : The preparation needs of young people for the move into adult health services ('transition'), has received extensive focus. The move from paediatric to adult healthcare is recognised as a challenging time for young people and their families: poor transition is associated with poor engagement with, or even complete disengagement from, adult health services, resulting in increased mortality and morbidity (DH, 2006). The way in which healthcare providers facilitate transition has come under increasing scrutiny with the publication of From the Pond into the Sea (CQC, 2104) and NICE Transition Guidelines (NICE, 2016); the inclusion of transition in CQC inspections; and the imposing of Commissioning for Quality and Innovation (CQUIN) targets on Trusts. Great Ormond Street Hospital for Children (GOSH) has initiated a Transition Improvement Project, facilitated by the Quality Improvement Team, which has resulted in the development of the 'Growing Up, Gaining Independence' (GUGI) programme. This strategy, unique to GOSH, will: Provide clinicians with a framework enabling them to provide developmentally appropriate care to all young people. Focus on helping all young people to develop the skills, knowledge and understanding associated with emerging adulthood. Ensure that, when necessary, young people and their families are adequately prepared for life after GOSH in adolescent or adult services. Empower all young people to become as independent of their healthcare as they can be irrespective of: whether they will transfer to specialist adolescent or adult services from GOSH illness, disability or prognosis the presence of a Learning Disability or Additional Need Will inform, support and involve parents and carers and enable them to be active participants in helping with the preparation for the changes to come.